Pengaruh gratitude journal terhadap subjective well-being pada remaja di yayasan pendidikan dan penyantunan anak yatim piatu - Wildahilyatul Imaniyah; Aisyatin Kamila (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
This study aims to determine the effect of Gratitude Journal on Subjective Well-Being in adolescents. This research uses the one group pretest-posttest design. The sample of this study was taken from the entire population, namely 20 adolescents who were given treatment for 30 days. The results of this study indicate that Gratitude Journal has a significant effect on Subjective Well-Being. This can be seen from the results of the analysis of the Paired Samples Test that has been carried out that the value of Sig. (2-tailed) .000 <0.05 indicates a significant difference between the pre-test variables and the post-test variables. This shows that there is a significant effect on the difference in the treatment given to each variable. The gratitude journal activity can be used as a way to increase subjective well-being.